Prognostic significance of preoperative abdominal fat thickness for pancreatic ductal adenocarcinoma - Shengqiang Zhang; Longjie Xu; Dekang Gao; Hongbo Zhang; Shaohua Wei (Discover Oncology)
Abstract Background The aim of this study was to investigate the clinical value of abdominal fat thickness (AFT) as a predictor of outcomes for patients with pancreatic ductal adenocarcinoma (PDAC). Methods Between August 2016 and March 2023, we retrospectively gathered data on 148 patients who underwent pancreaticoduodenectomy for PDAC at the Hepatobiliary Surgery Department of the Second Affiliated Hospital of Soochow University. We conducted a comparative analysis of laboratory results and radiological features between patients who developed postoperative pancreatic fistula (POPF) and those who did not. To identify predictive factors, we employed both univariate and multivariate analytical methods.Furthermore, we conducted prognostic assessments for overall survival (OS) and recurrence-free survival (RFS), taking into account AFT and various patient-related factors. Results POPF developed in 46 patients (31.1%). AFT > 74.2 mm was associated with a risk of POPF, high body mass index (BMI), operation time and soft pancreatic texture. Patients with POPF were significantly more likely to have high BMI (> 23.2 kg/m2),Intra-abdominal infection, and high AFT than patients without POPF. In the multivariate analysis, high AFT (OR,13.678;95% CI,1.848-101.236;p = 0.01) was the sole independent predictive factor for POPF. Compared with PDAC patients with low AFT values, high AFT patients showed significantly worse OS (HR,2.646; 95% CI, 1.516,4.618;p = 0.001) and RFS (HR, 3.612; 95% CI, 1.949,6.693; p < 0.001). Conclusion Patients who have experienced POPF have been shown to exhibit a high correlation with AFT. Among the various parameters examined, AFT has emerged as an independent predictive factor for clinically significant POPF. Additionally, our cohort study showed that AFT was associated with poor clinical outcomes in PDAC patients following surgical resection.